Approaches for Monitoring Warfighter Blast-related Exposures in Training to Develop Effective Safety Standards. (25th January 2021) - Kornguth, Steven; Rylander, Henry G; Smith, Spencer; Campbell, Julia; Steffensen, Steve; Arnold, David; Athey, Alex; Rutledge, J Neal
ABSTRACT: Introduction: Traumatic brain injuries are of concern to the sports and military communities because of the age of the participants and costly burden to society. To markedly reduce the impact of traumatic brain injury and its sequela (TBI-S), it is necessary to determine the initial vulnerability of individuals as well as identify new technologies that indicate early signs of TBI-S. Materials and Methods: Currently, diverse methods have been used by the authors and others in laboratory settings to reveal early signs of persistent TBI-S including simulation modeling of the effect of rapid deceleration on the deviatoric strain (shear force) imposed on specific brain regions, auditory evoked potential (AEP) measurements to determine injury to the auditory cortex optokinetic nystagmus (OKN) measures sensitive to vestibular trauma, and optical coherence tomography (OCT) measures that reveal changes in central visual function obtained noninvasively by examination of the retina. Results: Simulation studies provided technical information on maximal deviatoric strain at the base of the sulci and interface of gray and white matter consistent with results from neuropathology and from magnetic resonance imaging. The AEP and OKN reveal measurable injury to similar regions below the Sylvian fissure including auditory cortex and midbrain, and the OCT reveals changes to the retina consistent with forceful deceleration effects. Conclusions: The studies and results are consistent with prior work demonstrating that noninvasive tests may be sensitive to the presence of TBI-S, potentially in the training field as advances in the portability of test instruments are underway. When combined with baseline data gathered from individuals in quantitative form, key variances can emerge. Therefore, it is hypothesized that AEP, OKN, and OCT, taken together, may yield faster objective and quantitative neurophysiological measures serving as a "signature" of neural injury and more indicative of potentially persistent TBI-S—recommending larger scale longitudinal studies.